Influence of the day care, home and neighbourhood environment on young children's physical activity and health: protocol for the PLAYCE observational study. Issue 12 (8th December 2016) - Christian, Hayley; Maitland, Clover; Enkel, Stephanie; Trapp, Georgina; Trost, Stewart G; Schipperijn, Jasper; Boruff, Bryan; Lester, Leanne; Rosenberg, Michael; Zubrick, Stephen R
Abstract : Introduction: The early years are a critical period in a child's health and development, yet most preschool children fail to meet physical activity guidelines. Outside of the home and neighbourhood, children spend a large proportion of time within early childhood education and care (ECEC) services such as long day care. Research is required to determine how the design of day care outdoor (and indoor) spaces provides opportunities or constraints for physical activity. A significant evidence gap surrounds what objectively measured attributes of the home and neighbourhood environment influence preschoolers' physical activity. The PLAY Spaces & Environments for Children's Physical Activity (PLAYCE) study will empirically investigate the relative and cumulative influence of the day care, home and neighbourhood environment on preschoolers' physical activity. Methods and analysis: The PLAYCE study is a cross-sectional observational study (April 2015 to April 2018) of 2400 children aged 2–5 years attending long day care in metropolitan Perth, Western Australia. Accelerometers will measure physical activity with indoor physical activity measured using radio frequency identification. Global positioning systems will be used to determine outdoor location of physical activity around the home and neighbourhood for a subsample (n=310). The day care environment will be objectively measured using a validated audit tool. Other potential individual, social and physical environmental influences on preschoolers' physical activity will be collected by geographic information systems measures, parent and day care educator surveys. Ethics and dissemination: Ethical approval has been granted by The University of Western Australia Human Ethics Research Committee, approval number RA/4/1/7417. Findings will be published in international peer-reviewed journals and presented at international conferences. Key findings will be disseminated to stakeholders, collaborators, policymakers and practitioners working in the ECEC sector. Day care centre directors and parents will be given a summary report of the key findings.